2000
DOI: 10.1046/j.1365-2559.2000.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary neoplasms of the bladder are histological mimics of nontransitional cell primary tumours: clinicopathological and histological features of 282 cases

Abstract: The incidence of secondary bladder tumours is comparable to that of nontransitional cell primary tumours. Few secondary tumours have distinctive histological features, hence knowledge of the history and clinical investigations are particularly important in their diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
160
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(169 citation statements)
references
References 39 publications
3
160
0
6
Order By: Relevance
“…Previous studies have suggested a close histogenetic and pathogenetic relationship of primary adenocarcinoma of the urinary bladder and colorectal adenocarcinoma. [22][23][24][25][26] Our finding that cadherin-17 and GATA3 expression are very similar in these two tumor types supports this relationship (Table 2). However, positive nuclear and cytoplasmic immunostaining for b-catenin was evident in 95% of (21/ 22) primary and 92% of (23/25) secondary colorectal adenocarcinoma, in contrast to positive membranous and cytoplasmic staining for b-catenin in 92% of (23/25) primary adenocarcinomas of the urinary bladder and 100% of (11/11) urothelial carcinomas with glandular differentiation (Po0.001).…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have suggested a close histogenetic and pathogenetic relationship of primary adenocarcinoma of the urinary bladder and colorectal adenocarcinoma. [22][23][24][25][26] Our finding that cadherin-17 and GATA3 expression are very similar in these two tumor types supports this relationship (Table 2). However, positive nuclear and cytoplasmic immunostaining for b-catenin was evident in 95% of (21/ 22) primary and 92% of (23/25) secondary colorectal adenocarcinoma, in contrast to positive membranous and cytoplasmic staining for b-catenin in 92% of (23/25) primary adenocarcinomas of the urinary bladder and 100% of (11/11) urothelial carcinomas with glandular differentiation (Po0.001).…”
Section: Discussionsupporting
confidence: 74%
“…78 Urinary bladder invasion by prostatic carcinoma can also occur via lymphovascular invasion, without contiguous spread. 83 Results of ISUP survey and consensus meeting on pT4 disease A consensus in the survey considered direct rectal involvement by prostatic carcinoma to be pT4; 4% of the respondents to the survey would not stage the tumor and 1% would classify rectal involvement as M1 (Table 1).…”
Section: Results Of Isup Survey and Consensus Meeting On Lymphovasculmentioning
confidence: 99%
“…1 The distinction between primary and secondary adenocarcinomas of the bladder is important to clinical management, but may not always be straightforward to pathologists or clinicians. This is particularly true when the secondary adenocarcinoma is of colorectal origin, which may exhibit histologic features similar to or indistinguishable from primary bladder adenocarcinoma.…”
mentioning
confidence: 99%